2019
DOI: 10.3390/cells8101211
|View full text |Cite
|
Sign up to set email alerts
|

Increased Regeneration Following Stress-Induced Lung Injury in Bleomycin-Treated Chimeric Mice with CD44 Knockout Mesenchymal Cells

Abstract: CD44, an adhesion-molecule promoting cell-migration, is shown here to increase in stress conditions following bleomycin-induced apoptosis in alveolar epithelial cells (AECs), a main target of lung injury. In vivo, it inhibits tissue regeneration and leads to fibrosis. We show that some AECs survive by the ataxia-telangiectasia mutated kinase/ATM pathway, and undergo a CD44-mediated epithelial-mesenchymal transdifferentiation (EMT) with migratory capacities in vitro, and in vivo. We assessed apoptosis vs. proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, our study is the first to provide evidence concerning the relationship between miR-484 and drug-induced EMT in the lungs. Although several research groups, including our own, have elucidated bleomycin-induced EMT, different concentrations of bleomycin with a large range (0.4-120 µM) were used to induce EMT in those studies [14,[21][22][23][24][25][26]. For example, we used 60-µM bleomycin to induce EMT in A549 and A549/ABCA3 cells [14,24], while 0.4 µMbleomycin induced EMT-like phenotypical changes of RLE/Abca3 cells derived from rat normal alveolar epithelium [21].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to provide evidence concerning the relationship between miR-484 and drug-induced EMT in the lungs. Although several research groups, including our own, have elucidated bleomycin-induced EMT, different concentrations of bleomycin with a large range (0.4-120 µM) were used to induce EMT in those studies [14,[21][22][23][24][25][26]. For example, we used 60-µM bleomycin to induce EMT in A549 and A549/ABCA3 cells [14,24], while 0.4 µMbleomycin induced EMT-like phenotypical changes of RLE/Abca3 cells derived from rat normal alveolar epithelium [21].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that CD44, a type-I transmembrane glycoprotein, participates in inflammation and tissue fibrosis. 15 , 16 , 17 , 18 CD44 is widely expressed in most vertebrate cells, including fibroblasts. 19 , 20 , 21 As a cell adhesion molecule, CD44 plays a role in cell-cell and cell-matrix interactions 22 in various pathological processes, such as lymphocyte infiltration, 23 , 24 wound healing, and scar formation.…”
Section: Introductionmentioning
confidence: 99%
“…Such an epithelial–mesenchymal transdifferentiation leads to lung fibrosis. The proof of concept was achieved in bleomycin-treated chimeric mice injected with CD44 knockout mesenchymal cells [ 38 ].…”
mentioning
confidence: 99%